Five year changes in central and peripheral corneal thickness: The Shahroud Eye Cohort Study. Issue 5 (October 2016) - Hashemi, Hassan; Asgari, Soheila; Emamian, Mohammad Hassan; Mehravaran, Shiva; Fotouhi, Akbar
Highlights: Based on longitudinal study, corneal thickness decreased with age in 40–64 year olds. There was significantly greater thinning in the 8 mm periphery compared to the corneal center even after controlling for baseline thickness. The decline was mostly similar in both genders and independent of type of refractive error and IOP. Abstract: Purpose: To determine five year changes in corneal thickness from the apex to the 8 mm periphery and related factors through a longitudinal population-based study of middle-aged Iranians. Methods: In the first phase, 4670 of the 5190 participants, and in the second phase, 4666 of the 4737 participants were examined with the Pentacam. In this report, analysis was done on right eye data of 2509 people who had no diabetes, pterygium, or history of eye surgery, and their image quality was displayed as "ok". Thickness changes in different parts of the cornea and their relation with age, gender, refractive error, and intraocular pressure (IOP) were assessed using repeated measures analysis of covariance. Results: Corneal thickness reduced by 1.5 ± 11.7 μm in the apex, 2.6 ± 11.7 μm in the thinnest point, and 5.3 ± 12.2, 7.7 ± 14.3, and 11.4 ± 18.6 μm in peripheral rings of 2, 3, and 4 mm radius, respectively (all p < 0.001 with and without adjusting for baseline thickness). Of the studied thickness variables, only changes in the 4 mm ring significantly related with age (p < 0.001) and gender (p < 0.001); there was less change in older age and in men. Thickness changes were not related to refractive error or IOP (all p > 0.05). Conclusion: Corneal thickness decreased with age in this sample of 40–64 year olds. There was significantly greater thinning in the periphery compared to the corneal center even after controlling for baseline thickness. Results of this longitudinal study can be helpful in understanding age-related changes in the cornea and the eye.